Kecemasan Tokoh dalam Ranah 3 Warna Karya Ahmad Fuadi Kajian Psikologi Sastra - Annisauf Fadlilah Khoiri; Muhammad Rapi Tang; Hajrah Hajrah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The novel Ranah 3 Warna by Ahmad Fuadi discusses a lot about anxiety that is associated with Sigmund Freud's theory about personality dynamics in the form of anxiety. The discussion related to reality anxiety, neurotic anxiety and moral anxiety is interesting to study because there are still many people who experience anxiety but do not know the type of anxiety they are experiencing as is the case in the novel Ranah 3 Warna, describe the form of reality anxiety in the Anak Nusantara serial novel by Ahmad Fuadi, describe the form of neurotic anxiety in the novel Ranah 3 Warna by Ahmad Fuadi, describe the form of moral anxiety in the novel Ranah 3 Warna by Ahmad Fuadi. The method used in this study is a qualitative descriptive method. The data collection techniques used are documentation, reading techniques and note-taking techniques. Of the several forms of anxiety found in the novel, the words